2006
DOI: 10.1111/j.1460-9568.2006.04722.x
|View full text |Cite
|
Sign up to set email alerts
|

NF‐κB pathway: a target for preventing β‐amyloid (Aβ)‐induced neuronal damage and Aβ42 production

Abstract: Beta-amyloid (Abeta) peptides are key proteins in the pathophysiology of Alzheimer's disease (AD). While Abeta42 aggregates very rapidly to form early diffuse plaques, supplemental Abeta40 deposition is required to form mature neuritic plaques. We here investigated the role of nuclear factor-kappaB (NF-kappaB) pathway in Abeta40-mediated neuronal damage and amyloid pathology. In rat primary neurons and human postmitotic neuronal cells, the Abeta peptide induced a dose-dependent neuronal death, reduced the leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(115 citation statements)
references
References 70 publications
6
105
0
Order By: Relevance
“…Moreover, the c-Rel antisense made IL-1β exposure per se as toxic as the glutamate one (Pizzi et al, 2002). Further investigations confirmed that p50 and RelA subunit activation contributes to the apoptotic program in cells exposed to the β-amyloid peptide (Akama et al, 1998;Pizzi et al, 2005b;Valerio et al, 2006). In addition, the c-Rel-containing dimers p50/c-Rel and RelA/c-Rel are involved in neuroprotective effects elicited by S100B (Kögel et al, 2004), agonists at the metabotropic glutamate type 5 (mGlu5) receptors (Pizzi et al, 2005b;Sarnico et al, 2008b) or leptin (Valerio et al, 2009).…”
Section: Nf-κb In Neuron Survivalmentioning
confidence: 54%
See 1 more Smart Citation
“…Moreover, the c-Rel antisense made IL-1β exposure per se as toxic as the glutamate one (Pizzi et al, 2002). Further investigations confirmed that p50 and RelA subunit activation contributes to the apoptotic program in cells exposed to the β-amyloid peptide (Akama et al, 1998;Pizzi et al, 2005b;Valerio et al, 2006). In addition, the c-Rel-containing dimers p50/c-Rel and RelA/c-Rel are involved in neuroprotective effects elicited by S100B (Kögel et al, 2004), agonists at the metabotropic glutamate type 5 (mGlu5) receptors (Pizzi et al, 2005b;Sarnico et al, 2008b) or leptin (Valerio et al, 2009).…”
Section: Nf-κb In Neuron Survivalmentioning
confidence: 54%
“…Many studies supported the antiapoptotic effects of NF-κB (Koulich et al, 2001;Lezoualc′h et al, 1998;Maggirwar et al, 1998;Middleton et al, 2000) leading to neuronal resistance to excitotoxicity- (Yu et al, 1999) or Aβ-induced apoptosis (Kaltschmidt et al, 1999) in cultured neurons. Other studies demonstrated that the activation of NF-κB triggers neuronal degeneration after cerebral ischemia (Clemens et al, 1997;Schneider et al, 1999), mediates the glutamate-activated cell death program during excitotoxic insults to central neurons (Goffi et al, 2005;Grilli and Memo, 1999;Grilli et al, 1996;Pizzi et al, 2005a;Qin et al, 1999;Sarnico et al, 2008a) and the Aβ-mediated apoptosis (Valerio et al, 2006). In order to elucidate these incongruous data, we provided the first direct evidence about the dual role for NF-κB proteins as either cell death-or cell survival-promoting factors.…”
Section: Nf-κb In Neuron Survivalmentioning
confidence: 97%
“…It is suggested that APs trigger the apoptosis by interaction with various neuronal receptors and free radical production that activate different cell-death-signalling pathways (Yuan & Yankner, 2000). Valerio et al (2006) found that the activation of protein complex NF-kB in microglia plays a crucial role in AP-induced neuronal cell death. This signaling pathway can be modulated and significantly reduced by inhibition of the degradation of cytoplasmatic protein IkB that acts as an inhibitor of NF-kB.…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…The hallmarks of AD are extracellular plaques of -amyloid from cleavage of APP -amyloid precursor protein. A plaques induce NF-B signaling pathway which in microglia is involved in neuronal cell death [Valerio et al, 2006]. Yeung et al [2004] demonstrated that increased expression of SIRT1 led to reduced signaling mediated by NF-B, which had a highly neuroprotective infl uence and reduced infl ammation.…”
Section: Neuroprotectionmentioning
confidence: 99%